Comparison of bilateral medial rectus recession vs recession-resection as surgery for infantile esotropia - Gupta, Aman Kumar; Bajracharya, Kabindra; Yadav, Roshan Dev; Rai, Salma K.C. (Asian Journal of Medical Sciences, 2021)
Background: Infantile esotropia is misalignment of eyes from bifoveal fixation where surgical correction at an early age usually presents with good outcomes. Aims and Objective: To compare the surgical outcome between bilateral medial rectus recession (BMR) and recession- resection (RR) surgery in infantile esotropia. Materials and Methods: The study was conducted in Lumbini Eye Institute, Bhairahawa, from December 2017 to December 2018. Patients with infantile esotropia who underwent surgical correction were included in the study. Patients were examined pre operatively, and post operatively at day one and third month, where the angle of deviation was measured and the level of binocular single vision (BSV) was assessed. Data was entered and analyzed using the SPSS program. Results: Total 79 patients were included in the study out of which 33 underwent BMR and 46 underwent RR. The mean pre-operative angle by PBCT was 52.58 PD (SD ±15.468) in the BMR group and 47.83 PD (SD ±12.140) in the RR group. Post-operative deviation in the BMR group had angle <35 PD. In the RR group the post-operative deviation observed was <35 PD, whereas 1/46 patients had angle between 35-50 PD. All patients who had residual esotropia (ET) in either the BMR or RR group had a pre-operative angle above 50 PD. Pre-operatively 43% had fusion and rest of them had suppression. Post-operatively 40.5% had fusion, 15.2% had stereopsis and rest of them had suppression or BSV could not be assessed in them. Therefore, there was increase in BSV by 2.5% from fusion to stereopsis. Those who initially showed suppression or in whom the BSV could not be assessed pre-operatively now showed to have fusion or some stereopsis. In total there was 15.2% increase in stereopsis. Conclusion: Though cosmesis has been improved in most patients after strabismus surgery, BSV improvement was insignificant as most surgery was performed after attainment of visual maturity. No significant difference between BMR and RR was found in terms of improvement of angle of deviation and BSV.